1995
DOI: 10.1016/0735-1097(95)00126-k
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of insulin-glucose infusion followed by subcutaneous insulin treatment in diabetic patients with acute myocardial infarction (DIGAMI study): Effects on mortality at 1 year

Abstract: Insulin-glucose infusion followed by a multidose insulin regimen improved long-term prognosis in diabetic patients with acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
760
10
45

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,388 publications
(830 citation statements)
references
References 59 publications
15
760
10
45
Order By: Relevance
“…40 In combination with hypertension, Fukui et al 41 observed that DM accelerates LV diastolic dysfunction via renin-angiotensin system in hypertensive rats. Taken together, hypertension and DM could synergistically deteriorate diastolic function in human.…”
Section: Renin-angiotensin System and Opn Expressionmentioning
confidence: 99%
“…40 In combination with hypertension, Fukui et al 41 observed that DM accelerates LV diastolic dysfunction via renin-angiotensin system in hypertensive rats. Taken together, hypertension and DM could synergistically deteriorate diastolic function in human.…”
Section: Renin-angiotensin System and Opn Expressionmentioning
confidence: 99%
“…Moreover, a positive association between hyperglycaemia at the time of the event and subsequent mortality from myocardial infarction has been reported [3]. Although the mechanisms underlying this association are not fully understood, evidence that the use of insulin to lower glucose concentrations decreases mortality in patients with diabetes who have myocardial infarction [4] suggests that hyperglycaemia is not simply an epiphenomenon of a stress response. Consequently, hyperglycaemia at the time of myocardial infarction could be an important and potentially modifiable risk factor for poor outcome.…”
mentioning
confidence: 99%
“…It was suggested that there is probably a link between hyperglycemia and the lack of efficacy of GIK infusion in patients with ACS. Therapy with GIK has long been prescribed during the acute phase of myocardial infarction, but available data on its benefit have been controversial 2, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14. In the DIGAMI (Diabetes Mellitus, Insulin Glucose Infusion in Acute Myocardial Infarction) 1 study6 where GIK administration was associated with aggressive glucose lowering, a significant reduction in 1‐year mortality was demonstrated in patients with ST‐segment elevation myocardial infarction 4.…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms by which GIK could improve clinical outcomes in ACS includes the decrease of the amount of circulating free fatty acids while enhancing the use of glucose as the primary energy substrate for myocardial tissue 3, 4. Although early trials have shown some benefit of GIK treatment,5, 6, 7, 8, 9 other studies have not demonstrated such benefit 2, 10, 11, 12, 13, 14. It was suggested that the inability of GIK to improve outcome might partly be attributable to the tendency of GIK to increase serum glucose levels 15, 16.…”
mentioning
confidence: 99%